Problematika Hukum Masuknya Pihak Ketiga dalam Proses Pemeriksaan Sengketa Arbitrase di Indonesia - Desri Novian (LPPM Universitas Ekasakti Padang, 2023)
Arbitration disputes occasionally also have legal consequences for Parties outside the arbitration agreement who have legal relations in the implementation of the arbitration agreement and the object of the arbitration dispute, which is commonly referred to as a Third Party. Third Parties can be in the form of Parties that support or defend the interests of one of the Parties (joinder) or have their interests in the object dispute being examined and decided (intervention). However, the entry of a Third Party into an arbitration dispute lawsuit, the provisions of the limiting conditions must be agreed upon by the Parties and must be approved by the Arbitrator or Arbitral Tribunal. Based on this, the study analyzed the conditions for the entry of third parties into the arbitral dispute lawsuit process regarding the 1958 New York Convention, UNCITRAL Model Law on International Commercial Arbitration, Law No. 30 of 1999, the provisions of arbitration law in several countries and refer to the provisions of the Civil Procedure Code in Indonesia. This research was conducted using a qualitative method and is normative juridical by reviewing and comparing one regulation with another. The results of the research show that there is another form of third party that called intervention for legal obligation and show that Article 30 of Law no. 30 of 1999 is too rigid in applying the principle of personality and party autonomy so that the obligation to obtain agreement from the parties results in third parties having minimal opportunities to be able to enter as parties in the arbitration dispute examination.